The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/marc.201600092
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Controlled Polymers via Simultaneous Living Anionic Copolymerization of Competing Monomers

Abstract: Natural macromolecules, i.e., sequence-controlled polymers, build the basis for life. In synthetic macromolecular chemistry, reliable tools for the formation of sequence-controlled macromolecules are rare. A robust and efficient chain-growth approach based on the simultaneous living anionic polymerization of sulfonamide-activated aziridines for sequence control of up to five competing monomers resulting in gradient copolymers is presented. The simultaneous azaanionic copolymerization is monitored by real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 29 publications
5
83
1
Order By: Relevance
“…StMAz showed similar reactivity to previously reported aziridine monomers, which allowed us to prepare copolymers with nonfunctional aziridines to further adjust the degree of functionalization. In addition, the free radical polymerization of StMAz leaves the aziridine‐group untouched as a potential receptive for nucleophiles.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…StMAz showed similar reactivity to previously reported aziridine monomers, which allowed us to prepare copolymers with nonfunctional aziridines to further adjust the degree of functionalization. In addition, the free radical polymerization of StMAz leaves the aziridine‐group untouched as a potential receptive for nucleophiles.…”
Section: Introductionsupporting
confidence: 67%
“…First, the variation of the alkyl chain at the 2‐position of the aziridine ring allows to attach functional or solubilizing groups. We demonstrated that steric groups such as C‐10 chains or bulky phenyl groups do not hamper the polymerization . In addition, the electron withdrawing group, which is attached to the aziridine ring by a cleavable sulfonamide, can be used as a handle to control chemical function .…”
Section: Resultsmentioning
confidence: 98%
“…We combined the monomers 3‐VCA, styrene, and 4‐VCA with the strongest expected gradients for a 1 H‐NMR copolymerization kinetics experiment (Scheme ). Copolymerization kinetics of multiple monomers has only been rarely reported and is entirely novel for carbanionic terpolymerization …”
Section: Resultsmentioning
confidence: 99%
“…Though DPE derivatives have been widely used to synthesize in‐chain functionalized polymers, how the DPE units are distributed along the polymer chain is still an interesting challenge for polymer chemists who are focused on the field of LAP. For its special characteristic in living anionic copolymerization, we used the timing sample method (which also has been widely utilized to carry out the kinetic study and investigate the change of chemical compositions during LAP) under high vacuum conditions to investigate the sequential distribution of DPE units in a chain. Through the characterization of a series of samples taken with 1 H NMR, size exclusion chromatography (SEC) and MALDI‐TOF‐MS at different times during the copolymerization, the continuous change of composition and molecular weight can be obtained, and the statistical sequence of the DPE units in the chain can be exactly characterized.…”
Section: Sequence Determinationmentioning
confidence: 99%